The strategy of Inclusive University: a research and development work for Inclusive Excellence - Rayman, Julianna (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The „Inclusive University” strategic proposal was established as an initiative of quality development at the University of Pécs (PTE) in the autumn of 2015. The proposal was aiming to improve the academic excellence of PTE with creating a diverse, inclusive and equity educational environment. The present article summerizes the stategic proposal’s main goals, the concept – Inclusive Excellence – behind it, and the (working) process of creating it. By having a sight into the way of formulating the proposal we can understand the it’s methodology, and meanwhile we can have the chance to get to know the theoretical literature and the national adaptational opportunity of a modern approach.